LIP PRINT PATTERN ON DIFFERENT MEDIAS: A FORENSIC IDENTIFICATION TOOL - shah, Ukshan Parvez; Noor, Farida (Journal of Forensic Medicine and Toxicology, 2021)
Role of lip prints in identification is very vast. Study of lip prints is known as cheiloscopy1.lip prints are wrinkles or grooves present in the transition zone of human lip between inner labial mucosa and outer skin. These wrinkles or grooves present on the lips have been named by Tsuchihashi as “sulci labiorum rubrorum”2. Identification through lip prints is same as finger print. As finger prints are used for absolute identification, similarly lip prints are used for the same. But nowadays identification through lip prints is gaining attention as criminals are taking precautions like the use of gloves or silicon thumbs, so that their finger prints may not be identified. Like finger prints, lip prints are also unique to the individual. The location of lip print at the scene of crime gives much valuable information about the individual and his habits e.g. lip prints on drinking glass or on a cigarette.
Keywords: Lip prints; Identification